STUDENTS’ PERCEPTIONS OF THE IMPLEMENTATION OF KAHOOT! IN ENGLISH LANGUAGE TEACHING - Laily Mahbubah; Syafiul Anam (Undiksha Press, 2022)
A paradigm of integrating technology in education has been reaching increasing attention in past decades, one of which is by implementing gamification (the use of game-like features in non-game contexts) in English Language Teaching (ELT). This descriptive qualitative study explores how 23 secondary students in Indonesia perceived the strategy (Kahoot! application) in the classroom activities to support their learning activities which were divided into two: brainstorming and Kahoot! implementation as the main learning activity in the classroom. The data was derived from questionnaire and interview section. The finding shows that Kahoot! motivates and engages students in the learning process. It covers three dimensions of students’ engagement, namely: cognitive, emotional, and behavioral engagement. However, internet connection becomes a vital factor that has to be considered to create the success of Kahoot integration in teaching and learning activities. Keywords: Gamification, Kahoot!, English Language Teaching, students’ perception